Analisis Variasi Bahasa Pada Artikel Berita di Media Online Kompas.Com Periode Bulan September-November 2022 - Vike Primadani; Teguh Suharto; Dwi Rohman Soleh (Wewarah: Jurnal Pendidikan Multidisipliner, 2023)
The purpose of this study is to describe the language variations of news articles on the online media kompas.com. The approach used is a qualitative approach using language analysis methods. The data source used comes from kompas.com news articles taken from several rubrics that meet the requirements in the analysis process. The data collection technique uses theoretical triangulation. The results of this study indicate that language variations and forms of language variations in the use of sentences. Language variations include 1) based on the speaker's point of view 2) the speaker's point of view 3) the topic of conversation. The form of language variation is based on 1) the use of direct sentences 2) adverbs of time and place 3) additional vocabulary. This research can be used in the field of language.